Pea (Pisum sativum L.): the uneasy fate of the first genetical object - O. E. Kosterin (Вавиловский журнал генетики и селекции)
Pea (Pisum sativum L.) is an important vegetable and forage crop capable of improving soils via symbiotic nitrogen fixation. It is of special importance in Russia as a crop adapted to high latitudes and an inexpensive source of plant protein. In addition, pea is the first genetical object used in famous G. Mendel’s experiments. The first translocation in the history of genetics was also found in pea. Pea generation time can be shortened to 35 days, which is comparable with Arabidopsis. However, small and hardly recognizable chromosomes hampered the development of pea cytogenetics, while recombination genetic maps remained inadequate until 1990s, when they were improved only with the aid of molecular methods. Two different notations for pea linkage groups and chromosomes as cytological objects still coexist. Recently, the whole toolbox of modern molecular methods of genetic analysis was applied to pea, including isozymes, RAPD-, SSR-, RFLP-, AFLP-, STS-, CAPS-, sCAPS-, and SNP-markers, as well as methods of reverse genetics including TILLING and virus-induced genomic silencing. Application of association mapping. Several transcriptome studies have been carried out in pea. Meanwhile, we await the completion of pea nuclear genome sequencing in 2016. For working out new molecular markers in pea, the synteny of its genome to the sequenced genome of Medicago truncatula is extensively used. Genetic transformation of pea is very difficult. Pea has been used as an experimental model for investigation of the following fundamental issues: the genetic control of symbiosis with nitrogen fixing bacteria, influence of variation in the histone H1 gene on the phenotype, mechanism of nuclear- cytoplasmic conflict in remote crosses, origin of B-chromosomes in plants, and genetic control of compound leaf morphology.